Positive electrode sheet, method for manufacturing the same, and battery
By introducing potassium supplement KpS and a polymer layer into the positive electrode of potassium-ion batteries, the problems of poor cycle stability and capacity loss of potassium-ion batteries are solved, and higher battery first efficiency and cycle performance are achieved.
Patent Information
- Application Number
- CN202510550175.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-28
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2045-04-28
AI Technical Summary
Potassium-ion batteries face challenges in terms of energy density and cycle life, including narrow voltage windows, electrode dissolution, irreversible capacity loss due to corrosion and byproducts, poor cycle stability and short-circuit problems, and insufficient initial coulombic efficiency, which cannot be effectively addressed by existing technologies.
The positive electrode structure includes a current collector, an active material layer, and a potassium supplement layer. The active material layer contains KNiaFebMncO2, KdNO2, or KxVy[(XOm)n]z, and the potassium supplement layer contains KpS and a polymer. The potassium supplement-polymer layer is formed by coating to improve the battery's first efficiency and cycle performance.
It effectively avoids material corrosion, improves battery first efficiency, enhances electrochemical activity and thermal stability, reduces side reactions, and improves cycle performance and manufacturability.
Smart Images

Figure CN120674454B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of batteries, specifically to a positive electrode sheet, a method for preparing the same, and a battery. Background Technology
[0002] In recent years, the shortage and uneven distribution of lithium resources have severely limited the widespread and sustainable application of this type of battery. Potassium-ion batteries have attracted widespread attention in recent years due to their abundant metal reserves. Moreover, K₂CO₃ is much cheaper than Li₂CO₃. Furthermore, aluminum foil can be used as a current collector in potassium-ion batteries, replacing copper foil in lithium-ion batteries. This not only significantly reduces the price of potassium-ion batteries but also lightens the weight of the current collector and solves the over-discharge problem. The Stokes radius of potassium ions... Compared to lithium-ion Potassium has the highest ion mobility and ionic conductivity in electrolytes. Based on these advantages, potassium-ion batteries are expected to replace lithium-ion batteries as the next generation of high-performance energy storage devices.
[0003] Current potassium-ion batteries still face significant challenges in terms of energy density and cycle life, including narrow voltage windows, electrode dissolution, corrosion, and unexpected byproducts. These fundamental issues can lead to irreversible capacity loss, poor cycle stability, and short circuits, severely limiting the potential of potassium-ion batteries. + Effective storage is crucial. Therefore, further improvements in cycle performance are needed to meet practical requirements. Existing technologies, such as those disclosed in CN109279626B, have certain drawbacks because they cannot prevent materials from being corroded by air during use. Furthermore, the initial coulombic efficiency of potassium-ion batteries is typically less than 70%, and this low initial efficiency also limits the overall performance of potassium-ion batteries. Summary of the Invention
[0004] In view of this, the present invention aims to provide a positive electrode sheet, a method for preparing the same, and a battery, to solve the problems of poor cycle stability, capacity loss, and short circuit in potassium-ion batteries in the prior art.
[0005] To solve the above-mentioned technical problems, this application is implemented as follows:
[0006] The present invention provides a positive electrode sheet, the positive electrode sheet comprising a current collector, an active material layer disposed on at least one surface of the current collector in the thickness direction, and a potassium supplement layer disposed on the active material layer;
[0007] The potassium supplement layer comprises a potassium supplement and a polymer, the potassium supplement comprising K p S, where 1 / 4 ≤ p ≤ 3;
[0008] The active material layer includes active materials, including KNi. a Feb Mn c O2, K d NO2 or K x V y [(XO m ) n z at least one of them; wherein 0≤a≤0.4, 0≤b≤0.6, 0<c≤0.6, a+b+c=1; N comprises at least one of Group VIIB elements and / or Group VIII elements, 0<d≤0.6; X is selected from at least one of P, S, Si and Group VB elements, 0<x≤1, 0≤y≤2, 2<m≤4, 0<n≤2, 0<z≤1.
[0009] Optionally, the active material comprises KNi a Fe b Mn c O2, K d NO2 or K x V y [(XO m ) n z at least one of them; wherein 0.1≤a≤0.3, 0.1≤b≤0.5, 0.1≤c≤0.5, a+b+c=1; N comprises at least one of Co, Ni and Mn, 0.1≤d≤0.5; X is selected from at least one of P, S, Si and V, 0.2≤x≤0.8, 0.2≤y≤1.5, 2.5≤m≤3, 0.5≤n≤1.5, 0.2≤z≤0.5.
[0010] Optionally, the molar ratio of the active material to the potassium supplement agent is 1:(0.5% to 5%), preferably 1:(2% to 4%); optionally, in the potassium supplement agent layer, the molar ratio of the potassium supplement agent to the polymer is 1:(240 to 2500), preferably 1:(2000 to 2400); optionally, the polymer comprises at least one of polyvinyl alcohol, polyvinylpyrrolidone, polytetrafluoroethylene, polyvinylidene fluoride and sodium carboxymethyl cellulose.
[0011] Optionally, the active material layer further comprises a first conductive agent and a binder; preferably, the mass ratio of the active material, the first conductive agent and the binder in the active material layer is (94-99):(1-5):(1-3), preferably (95-97):(2-4):(1.5-2.5); optionally, the potassium replenishing agent layer further comprises a second conductive agent; preferably, the mass ratio of the potassium replenishing agent and the second conductive agent in the potassium replenishing agent layer is (94-99):(1-5), preferably (96-98):(2-3); optionally, the first conductive agent and the second conductive agent each independently comprise at least one of conductive carbon black, acetylene black, graphene, conductive graphite, conductive carbon nanotubes and conductive carbon fibers; optionally, the binder comprises at least one of polytetrafluoroethylene, polyvinylidene fluoride and sodium carboxymethyl cellulose.
[0012] Optionally, the thickness of the active material layer is 0.5 to 2 mm; and / or, the thickness of the potassium replenishing agent layer is 0.5 to 2 mm.
[0013] In a second aspect, the present invention provides a method for preparing a positive electrode sheet, comprising the following steps:
[0014] S1. coating a first slurry on at least one surface of a current collector in the thickness direction and performing a first drying treatment to obtain a current collector provided with a first active material layer;
[0015] S2. coating a second slurry on the surface of the current collector provided with the first active material layer and performing a second drying treatment to obtain a first positive electrode sheet; subjecting the first positive electrode sheet to a rolling treatment and a third drying treatment;
[0016] Wherein the first slurry comprises an active material, and the active material comprises KNi a Fe b Mn c O2, K d NO2 or K x V y [(XO m ) n z at least one of them; wherein 0≤a≤0.4, 0≤b≤0.6, 0<c≤0.6, a+b+c=1; N comprises at least one of Co, Ni and Mn, 0<d≤0.6; X is selected from at least one of P, S, Si and V, 0<x≤1, 0≤y≤2, 2<m≤4, 0<n≤2, 0<z≤1;
[0017] The second slurry comprises a potassium replenishing agent and a polymer, and the potassium replenishing agent comprises K p S, wherein 1 / 4≤p≤3.
[0018] Optionally, the preparation step of the first slurry includes: mixing the active material, the first conductive agent, the binder, and the first solvent, and then performing a first dispersion treatment; and / or, the preparation step of the second slurry includes: mixing the potassium supplement, the second conductive agent, and the second solvent, and then performing a second dispersion treatment to obtain an intermediate slurry; mixing the polymer and the third solvent, and then performing a third dispersion treatment to obtain a polymer solution; and mixing the intermediate slurry and the polymer solution; Optionally, the first solvent includes N-methylpyrrolidone; Optionally, the second solvent includes N-methylpyrrolidone; Optionally, the third solvent includes water.
[0019] Optionally, in step S1, the temperature of the first drying treatment is 80–120°C; and the time of the first drying treatment is 1–3 hours.
[0020] Optionally, in step S2, the temperature of the second drying treatment is 80-120°C; the time of the second drying treatment is 1-3 hours; Optionally, in step S2, the temperature of the third drying treatment is 60-80°C; the time of the third drying treatment is 8-16 hours.
[0021] A third aspect of the present invention provides a battery comprising a positive electrode sheet, wherein the positive electrode sheet is the positive electrode sheet described above or a positive electrode sheet prepared according to the preparation method described above.
[0022] The beneficial technical effects of the present invention through the above technical solution are as follows:
[0023] (1) The positive electrode of the present invention includes a current collector, an active material layer, and a potassium supplement layer, wherein the active material in the active material layer includes KNi a Fe b Mn c O2, K d NO2 or K x V y [(XO m ) n ] z The potassium supplement layer includes a potassium supplement and a polymer, and the potassium supplement includes K p S. This positive electrode effectively avoids the problem of material corrosion by air during use, thus affecting capacity; by introducing a potassium supplement into the positive electrode, the battery's initial efficiency can be effectively improved. Compared with potassium supplementation at the negative electrode, it is safer and more environmentally friendly. Potassium supplement K... p S exhibits excellent electrical conductivity and thermal stability, as well as high electrochemical activity, resulting in outstanding lithium replenishment performance with minimal side effects. Furthermore, a polymer is introduced into the outer layer of the positive electrode. This polymer layer prevents side reactions between the positive electrode material and the electrolyte during cycling, further improving cycle performance.
[0024] (2) The method for preparing the positive electrode of the present invention involves using a material containing active substance KNi a Fe b Mn c O2, K d NO2 or K x V y [(XO m ) n ] z The slurry and containing potassium supplement K p The positive electrode is obtained by coating the slurry of S and polymer sequentially; the coating process is simplified and manufacturability is improved by sequentially setting the active material layer and the potassium supplement-polymer layer and mixing the polymer and potassium supplement during the preparation process.
[0025] Other features and advantages of the present invention will be described in detail in the following detailed description section. Attached Figure Description
[0026] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof.
[0027] Figure 1 The diagram shown is a schematic diagram of the positive electrode sheet of the present invention.
[0028] Explanation of reference numerals in the attached figures:
[0029] 10-current collector;
[0030] 20-Active substance layer;
[0031] 30-Potassium supplement layer. Detailed Implementation
[0032] This invention discloses a positive electrode sheet, its preparation method, and a battery. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired result. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The methods and applications of this invention have been described through preferred embodiments. Those skilled in the art can clearly modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.
[0033] In the description of this invention, the list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0034] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0035] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0036] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0037] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0038] To address the problems of poor cycle stability, capacity loss, and short circuits in existing potassium-ion batteries, this invention employs the following technical solution:
[0039] The present invention provides a positive electrode sheet, the positive electrode sheet comprising a current collector 10, an active material layer 20 disposed on at least one surface in the thickness direction of the current collector, and a potassium supplement layer 30 disposed on the active material layer;
[0040] The potassium supplement layer comprises a potassium supplement and a polymer, the potassium supplement comprising K p S, where 1 / 4 ≤ p ≤ 3;
[0041] The active material layer includes active materials, including KNi. a Fe b Mn c O2, K dNO2 or K x V y [(XO m ) n z at least one of them; where 0≤a≤0.4, 0≤b≤0.6, 0<c≤0.6, a+b+c=1; N includes at least one of Group VIIB elements and / or Group VIII elements, 0<d≤0.6; X is selected from at least one of P, S, Si and Group VB elements, 0<x≤1, 0≤y≤2, 2<m≤4, 0<n≤2, 0<z≤1.
[0042] The positive electrode sheet of the present invention comprises a current collector, an active material layer and a potassium supplementing agent layer, wherein the active material in the active material layer comprises KNi a Fe b Mn c O2, K d NO2 or K x V y [(XO m ) n z , the potassium supplementing agent layer comprises a potassium supplementing agent and a polymer, the potassium supplementing agent comprises K p S. The positive electrode sheet can effectively avoid the problem that the material is corroded by air during use and thus affects the capacity; by introducing the potassium supplementing agent into the positive electrode sheet, the first efficiency of the battery can be effectively improved, which is safer and more environmentally friendly compared with potassium supplementing at the negative electrode. The potassium supplementing agent K p S has excellent electrical conductivity and thermal stability, also has high electrochemical activity, outstanding potassium supplementing effect and low side effects. At the same time, a polymer is further introduced into the outer layer of the positive electrode sheet, and the formed polymer layer can avoid side reactions between the positive electrode material and the electrolyte during the cycle, so that the cycle performance is further improved.
[0043] According to the present invention, the active material may include KNi a Fe b Mn c O2, K d NO2 or K x V y [(XO m ) n z at least one of them; where 0.1≤a≤0.3, 0.1≤b≤0.5, 0.1≤c≤0.5, a+b+c=1; N may include at least one of Co, Ni and Mn, 0.1≤d≤0.5; X may be selected from at least one of P, S, Si and V, 0.2≤x≤0.8, 0.2≤y≤1.5, 2.5≤m≤3, 0.5≤n≤1.5, 0.2≤z≤0.5.
[0044] According to the present invention, the molar ratio of the active material to the potassium supplement can be 1:(0.5% to 5%). In this invention, a suitable molar ratio of the active material to the potassium supplement helps to balance battery performance and cost. As an example, the molar ratio of the active material to the potassium supplement can be any value from 1:0.5%, 1:1%, 1:1.5%, 1:2%, 1:2.5%, 1:3%, 1:3.5%, 1:4%, 1:4.5%, and 1:5%, or any value within the range of any pair of the above values. In this invention, if the molar ratio of the active material to the potassium supplement is too high, it will lead to insufficient potassium supplementation and insufficient modification effect; if the molar ratio of the active material to the potassium supplement is too low, it will lead to potassium supplement redundancy, reducing energy density, increasing battery cost, and even increasing side reactions and deteriorating battery performance. Preferably, the molar ratio of the active material to the potassium supplement is 1:(2% to 4%).
[0045] According to the present invention, in the potassium supplement layer, the molar ratio of the potassium supplement to the polymer can be 1:(240-2500). As an example, in the potassium supplement layer, the molar ratio of the potassium supplement to the polymer can be any value selected from 1:250, 1:400, 1:500, 1:800, 1:1000, 1:1500, 1:2000, and 1:2500, or any value within the range formed by any pair of the above values. Preferably, in the potassium supplement layer, the molar ratio of the potassium supplement to the polymer is 1:(2000-2400).
[0046] For example, the polymer includes at least one of polyvinyl alcohol, polyvinylpyrrolidone, polytetrafluoroethylene, polyvinylidene fluoride, and sodium carboxymethyl cellulose.
[0047] According to the present invention, the active material layer may further include a first conductive agent and a binder.
[0048] According to the present invention, the mass ratio of the active material, the first conductive agent, and the binder in the active material layer can be (94-99):(1-5):(1-3). As an example, the mass ratio of the active material, the first conductive agent, and the binder in the active material layer can be any value from 94:1:1, 94:1:3, 94:2:1, 94:2:2, 94:2:3, 95:3:2, 96:4:1, 97:1:1, 97:3:2, 98:2:3, and 98:3:3, or any value within the range of any pair of the above values. Preferably, the mass ratio of the active material, the first conductive agent, and the binder in the active material layer is (95-97):(2-4):(1.5-2.5).
[0049] According to the present invention, the potassium supplement layer may further include a second conductive agent.
[0050] According to the present invention, the mass ratio of potassium supplement and the second conductive agent in the potassium supplement layer can be (94-99):(1-5). As an example, the mass ratio of potassium supplement and the second conductive agent in the potassium supplement layer can be any value from 94:1, 94:2, 95:3, 96:4, 97:1, 97:3, 98:2, and 98:3, or any value within the range of any pair of the above values. Preferably, the mass ratio of potassium supplement and the second conductive agent in the potassium supplement layer is (96-98):(2-3).
[0051] For example, the first conductive agent and the second conductive agent each independently include at least one of conductive carbon black, acetylene black, graphene, conductive graphite, conductive carbon nanotubes, and conductive carbon fibers.
[0052] For example, the adhesive includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, and sodium carboxymethyl cellulose.
[0053] According to the present invention, the thickness of the active material layer can be 0.5–2 mm. In this invention, a suitable thickness of the active material layer helps to balance battery performance and processing stability. As an example, the thickness of the active material layer can be any value selected from 0.5 mm, 0.8 mm, 1 mm, 1.2 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.9 mm, and 2 mm, or any value within a range formed by any two of the above values. In this invention, if the thickness of the active material layer is too thin, it will increase processing difficulty and cause performance deviations from expectations; if the thickness of the active material layer is too thick, it will lead to poor electrolyte wetting and ion transport efficiency, affecting battery performance.
[0054] According to the present invention, the thickness of the potassium replenishment layer can be 0.5–2 mm. In this invention, a suitable thickness of the potassium replenishment layer helps to balance interface protection and battery performance. As an example, the thickness of the potassium replenishment layer can be any value selected from 0.5 mm, 0.8 mm, 1 mm, 1.2 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.9 mm, and 2 mm, or any value within the range formed by any two of the above values. In this invention, if the thickness of the potassium replenishment layer is too thin, the interface protection effect will be weakened; if the thickness of the potassium replenishment layer is too thick, the ion transport impedance will increase, further affecting battery performance.
[0055] A second aspect of the present invention provides a method for preparing a positive electrode sheet, comprising the following steps:
[0056] S1. The first slurry is coated on at least one surface in the thickness direction of the current collector and subjected to a first drying treatment to obtain a current collector with a first active material layer.
[0057] S2. coating the second slurry on the surface of the current collector provided with the first active material layer and performing a second drying treatment to obtain a first positive electrode sheet; subjecting the first positive electrode sheet to a rolling treatment and a third drying treatment;
[0058] wherein the first slurry comprises an active material, and the active material includes KNi a Fe b Mn c O2, K d NO2 or K x V y [(XO m ) n z at least one of them; wherein 0≤a≤0.4, 0≤b≤0.6, 0<c≤0.6, a+b+c=1; N includes at least one of Co, Ni and Mn, 0<d≤0.6; X is selected from at least one of P, S, Si and V, 0<x≤1, 0≤y≤2, 2<m≤4, 0<n≤2, 0<z≤1;
[0059] the second slurry comprises a potassium supplement agent and a polymer, and the potassium supplement agent includes K p S, where 1 / 4≤p≤3.
[0060] In the method for preparing the positive electrode sheet of the present invention, the slurry containing the active material KNi a Fe b Mn c O2, K d NO2 or K x [(XO m ) n z and the slurry containing the potassium supplement agent K p S and the polymer are sequentially coated to obtain the positive electrode sheet; by sequentially arranging the active material layer and the potassium supplement agent-polymer layer, the problem that the positive electrode sheet is corroded by air during use and thus the capacity is affected can be effectively avoided; meanwhile, the method of mixing and coating the polymer and the potassium supplement agent in the preparation process simplifies the coating process and improves manufacturability; introducing the potassium supplement agent on the positive electrode side can further improve the first efficiency of the battery, which is safer and more environmentally friendly than introducing the potassium supplement agent on the negative electrode; in addition, the polymer layer formed by the polymer coated on the outer layer can effectively avoid side reactions between the positive electrode material and the electrolyte during the cycle, so that the cycle performance is further improved, that is, the positive electrode sheet has the characteristics of high first efficiency and good cycle performance at the same time.
[0061] Optionally, the preparation step of the first slurry includes: mixing the active material, the first conductive agent, the binder and the first solvent, and then performing a first dispersion treatment.
[0062] Optionally, the preparation step of the second slurry includes: mixing the potassium supplement, the second conductive agent, and the second solvent and then performing a second dispersion treatment to obtain an intermediate slurry; mixing the polymer and the third solvent and then performing a third dispersion treatment to obtain a polymer solution; and mixing the intermediate slurry and the polymer solution.
[0063] Optionally, the first solvent includes N-methylpyrrolidone.
[0064] Optionally, the second solvent comprises N-methylpyrrolidone.
[0065] Optionally, the third solvent includes water.
[0066] According to the present invention, in step S1, the temperature of the first drying treatment can be 80-120°C; the time of the first drying treatment can be 1-3 hours. As an example, in step S1, the temperature of the first drying treatment can be any value from 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, and 120°C, or any value within the range formed by any two of the above values; the time of the first drying treatment can be any value from 1 hour, 1.5 hours, 2 hours, 2.5 hours, and 3 hours, or any value within the range formed by any two of the above values.
[0067] According to the present invention, in step S2, the temperature of the second drying treatment can be 80-120°C; the time of the second drying treatment can be 1-3 hours. As an example, in step S2, the temperature of the second drying treatment can be any value from 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, and 120°C, or any value within the range formed by any two of the above values; the time of the second drying treatment can be any value from 1 hour, 1.5 hours, 2 hours, 2.5 hours, and 3 hours, or any value within the range formed by any two of the above values.
[0068] According to the present invention, in step S2, the temperature of the third drying treatment can be 60-80°C; the time of the third drying treatment can be 8-16 hours. As an example, in step S2, the temperature of the third drying treatment can be any value from 60°C, 62°C, 65°C, 68°C, 70°C, 72°C, 75°C, 78°C, and 80°C, or any value within the range formed by any pair of the above values; the time of the third drying treatment can be any value from 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, and 16 hours, or any value within the range formed by any pair of the above values.
[0069] A third aspect of the present invention provides a battery comprising a positive electrode sheet, wherein the positive electrode sheet is the positive electrode sheet described above or a positive electrode sheet prepared according to the preparation method described above.
[0070] The present invention will be further described in detail below through examples. All raw materials used in the examples are commercially available.
[0071] Example 1
[0072] The preparation of the positive electrode includes the following steps:
[0073] (1) 11.72g of active substance KNi 0.33 Fe 0.33 Mn 0.33 O2, 1.2g of conductive agent carbon black (Super-P) and 0.07g of binder polyvinylidene fluoride (PVDF) are uniformly dispersed in solvent N-methylpyrrolidone (NMP) to obtain a first slurry; the first slurry is coated onto an aluminum foil current collector and dried at 100°C for 2 hours to obtain a current collector with an active material layer.
[0074] (2) 2.03g of potassium supplement K2S and 0.21g of conductive carbon black (Super-P) were uniformly dispersed in the solvent N-methylpyrrolidone (NMP) to obtain an intermediate slurry; 3g of polyvinyl alcohol (PVA) was dissolved in 100mL of deionized water, stirred at 98°C for 2h until clear, and then cooled to 45°C. The intermediate slurry was added dropwise while stirring continuously for 15min to obtain a second slurry; the second slurry was coated on the surface of the current collector with the first active material layer, and then dried at 100°C for 2h to obtain a first positive electrode sheet; the first positive electrode sheet was rolled and then vacuum dried at 80°C for 24h to obtain a positive electrode sheet.
[0075] Example 2
[0076] The preparation method of the positive electrode is generally the same as that in Example 1, except that the amount of potassium supplement K2S added in the intermediate slurry is 5.08g and the amount of conductive agent carbon black (Super-P) added is 0.53g.
[0077] Example 3
[0078] The preparation method of the positive electrode is generally the same as that in Example 1, except that the amount of potassium supplement K2S added in the intermediate slurry is 10.18g and the amount of conductive agent carbon black (Super-P) added is 1.07g.
[0079] Example 4
[0080] The preparation method of the positive electrode is generally the same as that in Example 1, except that the amount of potassium supplement K2S added in the intermediate slurry is 15.25g and the amount of conductive agent carbon black (Super-P) added is 1.6g.
[0081] Example 5
[0082] The preparation method of the positive electrode is generally the same as that in Example 1, except that the amount of potassium supplement K2S added in the intermediate slurry is 20.34g and the amount of conductive agent carbon black (Super-P) added is 2.14g.
[0083] Example 6
[0084] The preparation method of the positive electrode is generally the same as that in Example 1, except that the potassium supplement in the intermediate slurry is K2S4, and the amount of potassium supplement K2S4 added in the intermediate slurry is 3.8g.
[0085] Example 7
[0086] The preparation method of the positive electrode is generally the same as that in Example 1, except that the active material in the first slurry is KNi. 0.3 Mn 0.4 Fe 0.3 O2, KNi, an active substance in the first slurry 0.3 Mn 0.4 Fe 0.3 The amount of O2 added is 5.87g; the amount of potassium supplement K2S added to the intermediate slurry is 11.77g, and the amount of conductive carbon black (Super-P) added is 1.24g.
[0087] Example 8
[0088] The preparation method of the positive electrode is generally the same as that in Example 1, except that the active material in the first slurry is KNi. 0.2 Fe 0.6 Mn 0.2 O2, KNi, an active substance in the first slurry 0.2 Fe 0.6 Mn 0.2 The amount of O2 added is 6g; the amount of potassium supplement K2S added to the intermediate slurry is 11.06g, and the amount of conductive carbon black (Super-P) added is 1.16g.
[0089] Example 9
[0090] The preparation method of the positive electrode is generally the same as that in Example 5, except that the active material in the first slurry is K. 0.5 MnO2, K, the active substance in the first slurry 0.5The amount of MnO2 added is 6g; the amount of potassium supplement K2S added to the intermediate slurry is 11.06g, and the amount of conductive carbon black (Super-P) added is 1.16g.
[0091] Example 10
[0092] The preparation method of the positive electrode is generally the same as that in Example 5, except that: the active material in the first slurry is K3V2(PO4)3, and the amount of K3V2(PO4)3 added in the first slurry is 6g; the amount of potassium supplement K2S added in the intermediate slurry is 11.06g, and the amount of conductive agent carbon black (Super-P) added is 1.16g.
[0093] Comparative Example 1
[0094] The preparation of the positive electrode includes the following steps:
[0095] (1) 11.72g of active substance KNi 0.33 Fe 0.33 Mn 0.33 O2, 1.2g of conductive agent carbon black (Super-P) and 0.07g of binder polyvinylidene fluoride (PVDF) are uniformly dispersed in solvent N-methylpyrrolidone (NMP) to obtain a first slurry; the first slurry is coated onto an aluminum foil current collector and dried at 80℃ for 2h to obtain a first positive electrode sheet; the first positive electrode sheet is rolled and then vacuum dried at 80℃ for 24h to obtain a positive electrode sheet.
[0096] Test Example 1
[0097] The preparation of a hybrid ion battery includes the following steps:
[0098] The positive electrode sheets prepared in Examples 1-8 and Comparative Example 1 were cut into 12mm circular positive electrode sheets. A potassium metal sheet with a diameter of 14mm and a thickness of 0.2mm was used as the negative electrode, a 0.1mol / L sodium perchlorate / ethylene carbonate / dimethyl carbonate (ethylene carbonate:dimethyl carbonate = 1:1) solution was used as the electrolyte, and a Whatman GF / F glass fiber with a diameter of 16mm was used as the separator. CR2032 coin cells were assembled in an argon-filled glove box. The cycle performance of the above cells was tested, and the test results are shown in Table 1.
[0099] Cyclic performance test:
[0100] (1) 0.1C first-cycle discharge capacity, 0.1C first-cycle coulombic efficiency:
[0101] First-cycle discharge capacity test: The hybrid-ion battery was left to stand at 25℃ for 30 minutes, then charged to 4V at a constant current of 0.1C, then charged to 0.05C at a constant voltage, and then discharged at 1.5V at a constant current of 0.1C. The discharge capacity at this time was recorded as the first-cycle discharge capacity. The battery was then charged to 4V at a constant current of 0.1C, and the charging capacity at this time was recorded as the first-cycle charging capacity. The initial coulombic efficiency = first-cycle discharge specific capacity / first-cycle charging specific capacity * 100%.
[0102] (2) Capacity retention rate over 100 cycles (C):
[0103] Cyclic performance test: The hybrid ion battery was left to stand at 25℃ for 30 minutes, charged to 4V at 1C constant current, then charged to 0.05C at constant voltage, and then discharged at 1.5V at 1C constant current. The discharge capacity at this time was recorded as the discharge capacity of the first cycle. After standing for 10 minutes, the capacity of the hybrid ion battery was recorded when the cycle reached 100 cycles.
[0104] Capacity retention rate on the 100th cycle = Discharge capacity on the 100th cycle / Discharge capacity on the 1st cycle.
[0105] Table 1
[0106]
[0107] As shown in Table 1, compared with the comparative example, the positive electrode prepared by this invention exhibits superior discharge capacity and capacity retention during charge and discharge. Furthermore, within the range of active materials, potassium supplements, and proportions provided by this invention, it demonstrates excellent electrical performance.
[0108] A comparative analysis of Examples 1 and Examples 2-5 reveals that Examples 2-5, compared to Example 1, all increased the amount of potassium supplementer K2S and conductive agent carbon black in the intermediate slurry. This means Examples 2-5 increased the amount of potassium reserve, and the proportion of conductive agent increased synchronously with the potassium supplement, providing more available active potassium for subsequent initial discharge and cycling processes. This improves the electronic conductivity of the intermediate layer, thereby enhancing the battery's cycle capacity retention. The positive electrode sheet prepared in Example 5 exhibited the best electrochemical performance, indicating that Example 5 provided a suitable reserve of active potassium, effectively replenishing the active potassium consumed by side reactions during the initial discharge and cycling processes. Therefore, it achieved better specific capacity utilization and cycle capacity retention.
[0109] A comparative analysis of Examples 1 and 6 reveals that Example 6, compared to Example 1, used potassium supplement K2S4 and increased the amount of potassium supplement added. This may be because the decomposition pathway of K2S4 is more complex, resulting in the release of more potassium. + The total amount or rate is lower than that of K2S, resulting in a slightly lower first effect.
[0110] A comparative analysis of Examples 1 and 7-8 shows that Examples 7-8, compared to Example 1, changed the active material to KNi. 0.3 Mn 0.4 Fe 0.3 O2 (Example 7), KNi 0.2 Fe 0.6 Mn 0.2 O2 (Example 8) may experience a slight decrease in capacity during cycling due to differences in the specific capacity and cycling performance of the active material.
[0111] A molecular comparison between Examples 5 and Examples 9-10 shows that Examples 9-10, compared to Example 5, changed the active substance to K. 0.5 MnO2 (Example 9) 、 K3V2(PO4)3 (Example 10) may experience a slight decrease in capacity during cycling due to differences in the specific capacity and cycling performance of the active material.
[0112] In summary, the positive electrode sheet prepared by this invention can significantly improve the capacity utilization and cycle performance of traditional potassium-ion batteries.
[0113] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A positive electrode sheet, characterized by, The positive electrode sheet comprises a current collector, an active material layer disposed on at least one surface of the current collector in the thickness direction, and a potassium replenishing agent layer disposed on the active material layer; The potassium supplement agent layer includes a potassium supplement agent and a polymer, the potassium supplement agent includes K p S, wherein 1 / 4≤p≤3; The active material layer includes an active material including KNi a Fe b Mn c O2, K d NO2, or K x V y [(XO m ) n ] z at least one of the group consisting of P, S, Si, and group VB elements, 0 < x ≤ 1, 0 ≤ y ≤ 2, 2 < m ≤ 4, 0 < n ≤ 2, and 0 < z ≤ 1.
2. The positive electrode sheet according to claim 1, characterized in that, The active substance comprises KNi a Fe b Mn c O2, K d NO2 or K x V y [(XO m ) n ] z at least one of wherein 0.1≤a≤0.3, 0.1≤b≤0.5, 0.1≤c≤0.5, and a+b+c=1; N includes at least one of Co, Ni and Mn, 0.1≤d≤0.5; X is selected from at least one of P, S, Si and V, 0.2≤x≤0.8, 0.2≤y≤1.5, 2.5≤m≤3, 0.5≤n≤1.5, 0.2≤z≤0.
5.
3. The positive electrode sheet according to claim 1, characterized in that, The molar ratio of the active material to the potassium replenishing agent is 1:(0.5%~5%); In the potassium replenishing agent layer, the molar ratio of the potassium replenishing agent to the polymer is 1:(240~2500); The polymer includes at least one of polyvinyl alcohol, polyvinylpyrrolidone, polytetrafluoroethylene, polyvinylidene fluoride and sodium carboxymethyl cellulose.
4. The positive electrode sheet according to claim 1, characterized in that, The active material layer further includes a first conductive agent and a binder; The potassium replenishing agent layer further includes a second conductive agent; The first conductive agent and the second conductive agent each independently include at least one of conductive carbon black, acetylene black, graphene, conductive graphite, conductive carbon nanotubes and conductive carbon fibers; The binder includes at least one of polytetrafluoroethylene, polyvinylidene fluoride and sodium carboxymethyl cellulose.
5. The positive electrode sheet according to claim 3 or 4, characterized in that, The molar ratio of the active material to the potassium replenishing agent is 1:(2%~4%); and / or, in the potassium replenishing agent layer, the molar ratio of the potassium replenishing agent to the polymer is 1:(2000~2400); and / or, the mass ratio of the active material, the first conductive agent and the binder in the active material layer is (94~99):(1~5):(1~3); and / or, the mass ratio of the potassium replenishing agent to the second conductive agent in the potassium replenishing agent layer is (94~99):(1~5).
6. The positive electrode sheet according to claim 1, characterized in that, The thickness of the active material layer is 0.5~2mm; and / or, the thickness of the potassium replenishing agent layer is 0.5~2mm.
7. A method for preparing a positive electrode sheet, characterized in that, comprising the following steps: S1, coating the first slurry on at least one surface of the current collector in the thickness direction and performing a first drying treatment to obtain the current collector provided with the first active material layer; S2, coating the second slurry on the surface of the current collector provided with the first active material layer and performing a second drying treatment to obtain a first positive electrode sheet; subjecting the first positive electrode sheet to rolling treatment and third drying treatment; wherein the first slurry includes an active material, the active material including KNi a Fe b Mn c O2, K d NO2, or K x V y [(XO m ) n ] z at least one of wherein 0≤a≤0.4, 0≤b≤0.6, 0<c≤0.6, and a+b+c=1; N includes at least one of Co, Ni and Mn, 0<d≤0.6; X is selected from at least one of P, S, Si and V, 0<x≤1, 0≤y≤2, 2<m≤4, 0<n≤2, 0<z≤1; The second slurry includes a potassium replenishing agent and a polymer, the potassium replenishing agent includes K p S, wherein 1 / 4 ≤ p ≤ 3.
8. The method for preparing a positive electrode sheet according to claim 7, characterized in that, the preparation step of the first slurry includes: mixing the active material, the first conductive agent, the binder and the first solvent and then performing a first dispersion treatment; and / or, The preparation steps of the second slurry include: mixing the potassium supplement, the second conductive agent, and the second solvent, and then performing a second dispersion treatment to obtain an intermediate slurry; mixing the polymer and the third solvent, and then performing a third dispersion treatment to obtain a polymer solution; and mixing the intermediate slurry and the polymer solution. The first solvent includes N-methylpyrrolidone; The second solvent includes N-methylpyrrolidone; The third solvent includes water.
9. The method for preparing the positive electrode sheet according to claim 7, characterized in that, In step S1, the temperature of the first drying treatment is 80~120℃; the time of the first drying treatment is 1~3h.
10. The method for preparing the positive electrode sheet according to claim 7, characterized in that, In step S2, the temperature of the second drying treatment is 80~120℃; the time of the second drying treatment is 1~3h. In step S2, the temperature of the third drying process is 60~80℃; the time of the third drying process is 8~16h.
11. A battery, characterized in that, The battery includes a positive electrode sheet, which is the positive electrode sheet according to any one of claims 1 to 6 or the positive electrode sheet prepared by the preparation method according to any one of claims 7 to 10.
Citation Information
Patent Citations
Nanosheet-shaped potassium-ion battery cathode material and its preparation method and potassium-ion battery
CN109279626B
Method for preparing novel potassium ion battery positive electrode material through two-step potassium supplementation
CN113336277A
Positive pole piece as well as preparation method and application thereof
CN113410427A
